Pemberdayaan UMKM melalui Pelatihan Pembuatan Sabun Sunlight di Desa Jandi Meriah - Dahliyanti Dahliyanti; Dewi Damayanti; Dini Gusmini; Arlina Arlina (Pusat Riset dan Inovasi Nasional, 2026)
Training programs are an effective strategy for empowering micro, small, and medium enterprises (MSMEs), particularly in rural areas. This study aims to analyze the effectiveness of training in producing Sunlight dishwashing liquid as an effort to empower MSMEs in Jandi Meriah Village. It also examines the impact of the training on improving community skills, expanding business development opportunities, and contributing to the village’s economic growth. This research employs a qualitative descriptive method with data collected through observation, in-depth interviews, and documentation. The findings show that the training significantly enhances participants’ technical knowledge and skills in producing dishwashing liquid, including understanding raw materials, formulation processes, and product packaging techniques. Additionally, the training fosters entrepreneurial motivation, strengthens basic managerial abilities, and opens opportunities for forming small business groups based on home industry activities. The socio-economic impacts include increased household income potential, strengthened community collaboration, and the emergence of new MSME initiatives. This study concludes that training in producing Sunlight dishwashing liquid is an effective empowerment instrument to enhance community capacity and strengthen the village economy, making it a sustainable program model for other rural areas.